Risk perception of blood transfusions – a comparison of patients and allied healthcare professionals - Jan A. Graw; Katja Eymann; Felix Kork; Martin Zoremba; Rene Burchard (BMC Health Services Research, 2018)
Abstract Background Due to an increasing demand in health care services plans to substitute selective physician-conducted medical activities have become attractive. Because administration of a blood transfusion is a highly standardized procedure, it might be evaluated if obtaining a patient’s consent for a blood transfusion can be delegated to allied healthcare professionals. Physicians and patients perceive risks of transfusions differently. However, it is unknown how allied healthcare professionals perceive risks of transfusion-associated adverse events. Methods Patients (n = 506) and allied healthcare professionals (n = 185) of an academic teaching hospital were asked to quantify their concerns about transfusions including five predefined transfusion-associated risks and their incidences. Results Blood transfusions were considered to be generally harmful by 10.9% of patients and 14.6% of caregivers (P = 0.180). Among all surveyed patients, 36.8% were worried about infection-transmissions (caregivers: 27.6%; P = 0.024). Compared to 5.4% of caregivers, 13.6% of patients believed infection-transmission was a frequent complication (P = 0.003). Caregivers ranked the risks of receiving an AB0-mismatch transfusion (caregivers: 29.7% vs. patients: 19.2%, P = 0.003) or a transfusion-associated allergic reaction (caregivers: 17.3% vs. patients: 11.1%, P = 0.030) significantly higher than patients and were aware of the high incidence of transfusion-associated fever (caregivers: 17.8% vs. patients: 8.3%, P < 0.001). Conclusion A significant part of interviewees perceived transfusions as a general health hazard. Patients perceived infection-transmissions as the most frequent and greatest transfusion-associated threat while caregivers focused on fatal AB0-mismatch transfusions and allergic reactions. Understanding the patients’ main concerns about blood transfusions and considering that these concerns might differ from the view of healthcare professionals might improve the process of shared decision making.